The obstructions scenario in evacuation: Simulation of urban evacuation vulnerability and its solution. - Nattasit Srinurak (2019)
A historic city with the deformed grid is one of the most extreme vulnerable to various type of disaster hazard. Labyrinth, narrowness combine with clusters of settlement is highly vulnerable in term of evacuation planning due to lost in orientation. These streets could easily be blocked by building rubble, vehicles, and congestion from evacuees. Evacuation route with obstruction has created the problem and decisive solution is needed. Thus, in this paper, the developed assessment of evacuation situation has been performed using agent-based simulation on an urban scale. Analysis of simulation demonstrated in different situations of obstruction. Vulnerable of obstruction measured by its total time, time to exit and accumulated number of evacuees, simultaneously. The result of research, the obstruction simulation revealed the vulnerable from the congestion of evacuee and overcapacity in evacuation places. Distinct evacuation increases from 682 seconds in no-obstruction to 2,638 seconds in the combined obstruction scenario. Afterward, the solution strategy scenario was simulated according to congestion location. The solution scenarios show performance with 970 seconds time of evacuation decreasing. An agent-based simulation shows geospatial-related of evacuation and able to create a viable solution for the historic city.